Optimal Revenue Generation Using Linear Programming: A Case Study of Dormaa East District Assembly - Ofori, Samuel (2014)
A thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Science degree in Industrial Mathematics,